Marine biodiversity baseline for Área de Conservación Guanacaste, Costa Rica: published records - Cortés Núñez, Jorge (2017)
The diversity of tropical marine organisms has not been studied as intensively as the terrestrial biota worldwide. Additionally, marine biodiversity research in the tropics lags behind other regions. The 43,000 ha Sector Marino of Área de Conservación Guanacaste (ACG, Marine Sector of Guanacaste Conservation Area), on the North Pacific coast of Costa Rica is no exception. For more than four decades, the terrestrial flora and fauna has been studied continuously. The ACG marine biodiversity was studied in the 1930’s by expeditions that passed through the area, but not much until the 1990’s, except for the marine turtles. In the mid 1990’s the Center for Research in Marine Science and Limnology (CIMAR) of the Universidad de Costa Rica (UCR) initiated the exploration of the marine environments and organisms of ACG. In 2015, ACG, in collaboration with CIMAR, started the BioMar project whose goal is to inventory the species of the marine sector of ACG (BioMar ACG project). As a baseline, here I have compiled the published records of marine ACG species, and found that 594 marine species have been reported, representing 15.5% of the known species of the Pacific coast of Costa Rica. The most diverse groups were the crustaceans, mollusks and cnidarians comprising 71.7% of the ACG species. Some taxa, such as mangroves and fish parasites are well represented in ACG when compared to the rest of the Costa Rican coast but others appear to be greatly underrepresented, for example, red algae, polychaetes, copepods, equinoderms, and marine fishes and birds, which could be due to sampling bias. Thirty species have been originally described with specimens from ACG, and 89 species are not known from other localities on the Pacific coast of Costa Rica except ACG. Most of the sampling has been concentrated in a few localities in Sector Marino, Playa Blanca and Islas Murciélago, and in the nearby waters of Bahía Santa Elena. In an effort to fill this gap, CIMAR is collaborating with ACG and a private foundation to start an inventory of the marine organisms of the conservation area. The project will be assisted by two marine parataxonomists, and all samples will be catalogued, photographed, bar coded and voucher specimens deposited at the Museo de Zoología, UCR. All the information will be available through Internet. It is anticipated that the BioMar project will fill many of the knowledge gaps and significantly more marine species will be encountered. This project could become a viable model for marine biodiversity inventories in other Costa Rican Conservation Areas (Áreas de Conservación) and in other countries.